HEAD MRI EXAMINATION PROCEDURE WITH CLINICAL INTRACRANIAL SPACE OCCUPYING LESION AT THE RADIOLOGY INSTALLATION OF DR. HASAN SADIKIN HOSPITAL BANDUNG - Utami, Lucky Restyanti Wahyu (Journal of Applied Health Management and Technology, 2025)
Background: MRI is radiological imaging using a magnetic field that can produce axial, sagittal and coronal images of organs, bones, soft tissue and the nervous system. The use of appropriate MRI parameters can reveal detailed anatomical and pathological images of body tissue. One of the pathologies that can be confirmed using an MRI examination is an intracranial space occupying lesion. Intracranial space occupying lesion is a medical term that describes a lesion that occupies space in the brain which can damage important brain structures and obstruct the flow of cerebrospinal fluid. The aim of this study was to determine the MRI head examination procedure with clinical intracranial space occupying lesion at the Radiology Installation of Dr. Hasan Sadikin Hospital, Bandung. Method: This type of research is descriptive qualitative research with a case study approach. Result: The research results obtained were a head MRI examination procedure with clinical intracranial space occupying lesion at the Radiology Installation of Dr. Hasan Sadikin Hospital, Bandung, which included special patient preparation. The examination was carried out using a 1.5 tesla MRI. The examination is carried out in the patient's supine and head first position. The examination is carried out by scanning pre-contrast media and post-contrast media. Conclusion: The MRI head examination procedure with a clinical intracranial space occupying lesion at the Radiology Installation of Dr. Hasan Sadikin Hospital, Bandung was considered to have been able to confirm the diagnosis.